Snr-based load-balanced scheme for routing in multipath abd hoc wireless network - Tan, Chee Kang. (Universiti Malaysia Sarawak (UNIMAS), 2011)
Ad hoc wireless networking is an omportant area of research in telecomunications field. Multipath routing of data in wireless envioment contributes to better performance of ad hoc wireless network , by enabling higher throughput beyond the capacity of taditional single path routing networks. However, multipath routing requires a more complex but efficient protocol to handle path selection. In this respect, one of the important parameters to determine quality of paths to be selected for routing is the node-to-node channel quality.